Radiation exposure dose of medical workers during radioguided sentinel lymph node biopsy - Jankulovska, Anamarija; Sazdova Danova, Irena; Manevska, Nevena; Stojanoski, Sinisa; Miladinova, Daniela (Tehran University of Medical Sciences, 2022)
Introduction: Radiation monitoring of professionally exposed workers is obligatory in nuclear medicine departments. The purpose of our study was to evaluate the radiation exposure dose received by medical workers during radioguided sentinel lymph node biopsy in breast cancer and endometrial cancer patients. Methods: Radiation exposure dose of medical staff was prospectively recorded during 35 radioguided sentinel lymph node biopsy procedures in a 6-month period. All patients received 4 mCi [99mTc]Tc-SENTI-SCINT on the day of surgery. Thermoluminescent dosimeters in the shape of a bracelet, ring and badge were used for recordings and data was compared to dose limits imposed by the regulations. Results: Mean time interval between activity administration and surgery was 223.63 min and mean duration of surgery was 142.5 min. The recorded 6-month cumulative dose was 0.33 mSv for the senior surgeon, 0.25 mSv for the surgeon's first assistant, 0.24 mSv for the anesthesiologist and 0.54 for both nuclear medicine physician and resident. The approximately equivalent dose for the surgical staff in each procedure was 9.7 µSv, 7.3 µSv and 7.05 µSv respectively, which means that the senior surgeon could perform 106 and 2127 sentinel lymph node biopsy procedures per year in order to reach the annual dose limit for a public member and a radiation worker. Conclusion: Occupational radiation exposure dose of medical staff during radioguided sentinel lymph node biopsy is low and under annual dose limits, requiring no routinely personal dosimetry for surgical staff performing the procedure.
Keywords: Radiation exposure dose; Dosimeter; Medical staff; Sentinel lymph node